Extended HLA‐G haplotypes in patients with age‐related macular degeneration. (20th August 2018) - Svendsen, S. G.; Nilsson, L. L.; Djurisic, S.; Funck, T.; Wu, C.‐L.; Faber, C.; Falk, M. K.; Singh, A.; Sørensen, T. L.; Carosella, E. D.; LeMaoult, J.; Hviid, T. V. F.; et al.
Abstract : This study aims to determine if genetic polymorphisms in the HLA‐G gene are associated with age‐related macular degeneration (AMD). HLA‐G is important for immunological tolerance, and it is also known to have angiogenic effects. Polymorphisms in the 5′‐upstream regulatory region and 3′‐untranslated region (UTR) of HLA‐G have been associated with a number of diseases, especially with respect to a 14 bp insertion/deletion (ins/del) polymorphism in the 3′UTR. Full gene sequencing was performed on a cohort of 146 AMD patients and 63 healthy controls aged ≥60 and HLA‐G haplotypes were determined. Analyses were performed on a publicly available gene expression dataset from the NCBI GEO database (accession number GSE29801) from which expression data for HLA‐G, ‐C, and ‐A were extracted. Analysis of the GEO dataset showed that both HLA‐G and ‐C were expressed in the back of the eye and that expression was upregulated in the macular area of AMD. No differences were observed between patients and controls when analyzing the distribution of haplotypes in the HLA‐G promoter, coding region, 3′UTR, or the 14 bp ins/del polymorphism of the 3′UTR. The increased expression of HLA‐G in the macula of AMD patients indicates a role of HLA‐G in the micro environment as part of the AMD pathogenesis. This is supported by the expression of HLA‐C, which has previously been shown to play a role in AMD. The HLA‐G haplotype distribution did not display any differences between AMD patients and controls.